(untitled) (Bangladesh Journal of Bioethics, 2013)
Being a scientist, especially a clinical research one, is a noble but tough job. Scientific job is different from other jobs in terms of working hour and pressure; they need more freedom in their job & research that also put lots of responsibility on them. Research is funded by public money and it is the responsibility of scientists to gain maximum output from it. Clinical research is very complex and involves the use of animal, microbial as well as human samples and volunteers which make it more prone to ethical scrutiny. Minority of researchers who commit fraudulent use of public money & unethical clinical practice threaten public support for science. Now a day, there is growing concern of public and politicians on the freedom of scientists and unethical scientific practice in clinical trials. The most efficient measures to prevent scientific misconduct are awarenessnotably, self-awareness education and transparency. Most of the developed countries have formulated their own guidelines to ensure proper utilization and ethical clinical research and trials. Bangladesh is still lagging behind in terms of regulation and monitoring of clinical research and trials. This review aims to make related peoples to be aware of the necessity of its own guidelines for clinical research and trials. DOI: http://dx.doi.org/10.3329/bioethics.v4i1.14266 Bangladesh Journal of Bioethics 2013; 4(1):30-34